1997
DOI: 10.1172/jci119491
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid hormone exerts disparate effects on osteoblast differentiation depending on exposure time in rat osteoblastic cells.

Abstract: It has been reported that PTH exerts bone-forming effects in vivo when administered intermittently. In the present study, the anabolic effects of PTH(1-34) on osteoblast differentiation were examined in vitro. Osteoblastic cells isolated from newborn rat calvaria were cyclically treated with PTH (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
219
5
7

Year Published

2002
2002
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 328 publications
(253 citation statements)
references
References 47 publications
22
219
5
7
Order By: Relevance
“…Error bars represent S.E. tured cells under osteogenic conditions with PTH or PBS for 6 h of every 48 h to stimulate osteoblast differentiation (53). In control osteoblasts, PTH increased mineralized nodule formation after 14 days, and as reported previously, deletion of G s ␣ led to markedly enhanced mineralization (35).…”
Section: Resultssupporting
confidence: 58%
“…Error bars represent S.E. tured cells under osteogenic conditions with PTH or PBS for 6 h of every 48 h to stimulate osteoblast differentiation (53). In control osteoblasts, PTH increased mineralized nodule formation after 14 days, and as reported previously, deletion of G s ␣ led to markedly enhanced mineralization (35).…”
Section: Resultssupporting
confidence: 58%
“…In contrast to the in vivo and in vitro evidence for a direct anti-mitotic action of short term exposure of osteoblast progenitors to PTH, osteogenic cell replication was stimulated by 6 hours of exposure to PTH or PTHrP in cultures established from the bone marrow [69] or calvaria [70] of young rats. In addition, treatment of embryonic chick periosteal cells with PTH for 5-30 minutes stimulated proliferation [71].…”
Section: Effects Of Intermittent Pth On the Replication And Differentmentioning
confidence: 59%
“…Some studies have found that PTH exerts anti-apoptotic actions in osteoblasts through PKA signaling (35,36). Others have reported that intermittent treatment with PTH stimulates bone anabolism through both PKA and PKC pathways in osteoblasts (37). However, it has been reported that PKC activity inhibits osteoblast differentiation (38).…”
Section: Discussionmentioning
confidence: 99%